A fuel cell / water electrolyzer catalyst mass production method and application
Through the all-solid phase preparation process, metal nanoparticles are prepared by inert gas protection and arc plasma deposition, and loaded and heat treated with activated carbon materials, solving the problems of solvent use and reaction control in the preparation of fuel cell/water electrolytic cell catalysts, and achieving efficient and environmentally friendly mass production of catalysts.
Patent Information
- Application Number
- CN202211636931.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-14
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2042-12-14
AI Technical Summary
The existing fuel cell/water electrolytic cell catalyst preparation process involves a large number of organic solvents, polymer surfactants, etc., resulting in problems such as low yield, high cost, high pollution and low performance.
Using an all-solid phase preparation process, the active metal target is melted under the protection of inert gas to form metal nanoparticles, and load and heat treatment with the enhanced activated carbon material to form a catalyst rich in active components on the surface.
Massive production of catalysts is achieved, material costs are reduced, pollution is avoided, and the stability and life of the catalyst is improved. At the same time, the difficulties in solvent use and reaction control in traditional processes are solved.
Abstract
Description
Technical Field
[0001] The invention relates to a fuel cell / water electrolysis cell catalyst batch production method and application, belonging to the technical field of electrocatalysis. Background Art
[0002] Traditional fossil energy is facing depletion and environmental pollution problems, and the development of new energy has become increasingly urgent. As an energy conversion device, proton exchange membrane fuel cells / water electrolyzers can directly convert chemical energy in fuels such as hydrogen and methanol into electrical energy. They have the characteristics of high energy density, high efficiency, and environmental friendliness. They are ideal power sources for electric vehicles and are also regarded as potential power sources in the future for portable power supplies and fixed power stations. They have always been a hot spot for research and development.
[0003] The catalysts in current proton exchange membrane fuel cells / water electrolyzers have always been a bottleneck problem in the localization of membrane electrodes. The preparation process of the catalyst is complicated and difficult to prepare in large quantities. In addition, the prepared domestic catalysts still face defects such as low performance and poor stability. The current preparation of Pt-based catalysts mainly adopts liquid phase reduction, impregnation reduction and other methods, involving a large amount of organic solvents. The process is cumbersome and harmful to the environment. The reducing agents used, such as NaBH4, have strong reducing properties and belong to the category of dangerous goods, which are not suitable for mass production applications. In addition, the current process uses ethylene glycol as an organic solvent and reducing agent. Due to its high viscosity, it is inconvenient to clean, making it impossible to achieve mass production of the catalyst and causing damage to the environment.
[0004] At the same time, alloy catalysts were developed based on platinum metal, but the preparation process still used the solvent thermal method. In later studies, vacuum sputtering and other methods gradually emerged, but this method is cumbersome and requires expensive magnetic field control equipment. At the same time, the use of organic solvents is not conducive to the mass production of catalysts.
[0005] In summary, many current catalyst preparation processes involve the use of high molecular surfactants or solvents, and the back-end also uses raw materials including strong acids and strong bases. On the one hand, the preparation cost is high, the pollution is large, and the preparation steps are complicated. On the other hand, the surface of the prepared catalyst is difficult to clean, and the catalyst performance is low and the life is short. Summary of the invention
[0006] The purpose of the present invention is to provide a fuel cell / water electrolyzer catalyst mass production method and application, aiming to solve the problems of low output, high cost, high pollution, low performance, etc. caused by a large amount of organic solvents, polymer surfactants, etc. involved in the catalyst preparation process.
[0007] In order to achieve the above object, the technical solution of the present invention is as follows:
[0008] One aspect of the present invention provides a method for mass production of a catalyst, the method comprising the following steps:
[0009] A. Melting the active metal target under the protection of inert gas, then placing it in a centrifugal oil mist collector or a filter oil mist collector and introducing inert gas at the same time, forming metal nanoparticles after cooling, and then separating the metal nanoparticles from the inert gas through a cyclone separator to finally obtain metal nanoparticles;
[0010] B. ball-milling and stirring the carbon material and introducing an activated gas for activation treatment to obtain a reinforced activated carbon material;
[0011] C. adding the metal nanoparticles obtained in step A to the enhanced activated carbon material obtained in step B, stirring and mixing by a planetary stirrer, so that the metal nanoparticles are loaded on the enhanced activated carbon material to obtain a loaded material;
[0012] D. The supported material obtained in step C is subjected to heat treatment in a mixed gas atmosphere to form a catalyst having a surface rich in active components.
[0013] In the above technical solution, further, the carbon material is one of XC-72R, EC300, EC600, graphene, and carbon nanotubes;
[0014] The active metal is any one of Pt, Ir, Pd, and Ru, or a combination of one or two of non-precious metals Co, Cu, Fe, Mo, and Mn.
[0015] In the above technical solution, further, the mass ratio of the active metal to the carbon material is 0.25-4.
[0016] In the above technical solution, further, in step A, the active metal target is melted by arc plasma deposition, and the discharge voltage of the arc plasma deposition is 100-400V and the capacitance is 200-2000μF;
[0017] The diameter of the metal nanoparticles is 2-5 nm;
[0018] The inert gas is nitrogen or argon.
[0019] In the above technical solution, further, in step B, the activation gas is a mixed gas of hydrogen and argon, wherein the volume fraction of hydrogen is 5%;
[0020] The ball mill stirring time is 1-5h.
[0021] In the above technical solution, further, in step C, the stirring mill and the planetary mill of the planetary agitator are both stirred for 1-5 hours.
[0022] In the above technical solution, further, in step D, the heat treatment temperature is 200-500°C, and the heat treatment time is 0.5-5h;
[0023] The mixed gas is a mixed gas of hydrogen and argon, wherein the volume fraction of hydrogen is 5-10%.
[0024] Another aspect of the present invention provides a catalyst obtained by the above preparation method, wherein the catalyst comprises an activated carbon material and an active metal component, wherein the mass content of the active metal component is 20-80%.
[0025] Another aspect of the present invention provides a use of the above catalyst in a fuel cell or a water electrolysis cell.
[0026] The present invention has the following beneficial effects:
[0027] 1. The present invention adopts a novel all-solid-phase preparation process. First, the all-solid-phase preparation process does not use organic solvents and surfactants in the preparation process, does not require a large-scale removal process in the later stage, and can be mass-produced. Second, the washing and drying steps are omitted, no pollution is caused, and strong acids and strong bases are not used as precipitants, avoiding the risk of corrosion and greatly reducing the material cost. Third, the preparation process of the prior art uses solvents in the preparation process, and the reaction process of each process section is microscopic and the time is uncontrollable, so continuous preparation cannot be achieved. The all-solid-phase preparation method of the present invention can not only successfully prepare a catalyst with high catalytic activity, but also adopts specific mature equipment control. The specific equipment and the method complement each other. The reaction process is direct and can be controlled according to the parameters of the equipment to control the reaction process and meet the material size requirements, etc. Therefore, a production line can be easily formed to achieve continuous preparation, which is more conducive to the preparation of large quantities of catalysts.
[0028] 2. The present invention is directed to a fully solid-phase preparation method, and simultaneously activates the carbon carrier material. During the reaction process of solid-phase material loading, the oxidation loss of the catalyst carbon carrier can be avoided, the specific surface area can be increased, and the contact area of the catalyst can be increased. Firstly, the corrosion resistance and stability of the carrier itself can be improved. Secondly, it is beneficial for two solid particles-metal nanoparticles to be smoothly loaded on the surface of the carrier and dispersed more evenly. Thirdly, the contact between the active component nanoparticles and the carrier is more firmly made, and thus the overall stability of the catalyst is better, the active component nanoparticles are not easy to fall off and lose, and the catalyst has a long service life.
[0029] 3. The present invention is directed to a fully solid-phase preparation method, which uses an activated gas treatment in which a mixture of hydrogen and argon is introduced. On the one hand, the radius of hydrogen molecules is small, and they can effectively enter the micropores of the carbon material, so that all the micropores of the carbon material are opened, increasing the specific surface area of the carbon material, and improving the loading amount and loading efficiency of the metal active components. In addition, the argon atmosphere prevents the carbon material from being oxidized by oxygen and destroying its electronic properties. This activation method is more conducive to the comprehensive activation of the solid-phase activated carbon in a closed cavity.
[0030] Furthermore, the carbon material is subjected to high-energy ball milling during the strengthening process. The carbon material is subjected to collision, impact, shearing and extrusion under the repeated impact of the grinding ball medium. The high-intensity and long-term grinding makes the carbon material fully uniform and refined, and finally becomes a powder with dispersed distribution of the reinforcement. In addition, it can also reduce the reaction activation energy, refine the grains, greatly improve the uniformity of carbon material particle distribution and the interface bonding with the metal active components, promote solid-state ion diffusion, induce low-temperature chemical reactions, thereby improving the density, electrical and thermal properties of the material. Therefore, the grinding process is accompanied by the introduction of gas, that is, high-intensity mechanical rolling is achieved while activation, so that the carbon material is continuously refined and dispersed in the closed chamber, which can make the powdered carbon material fully contact with the activated gas and realize the comprehensive activation of large quantities of carbon materials. That is, the two complement each other, making the activation more thorough and effective.
[0031] 4. In the all-solid-phase preparation process of the present invention, arc plasma deposition is used to prepare metal nanoparticles. On the one hand, the direct regulation function of pulse energy can be used to control the particle size during the preparation process to obtain particles of a reasonable size, thereby solving the practical difficulty of "if the particle size is too small, the nanoparticles are unstable and are prone to agglomeration or dissolution during use; if the particle size is too large, the specific surface area is small, which is not conducive to exerting high catalytic activity". This difficulty cannot be easily overcome in the solvent preparation method. At the same time, the direct regulation function of pulse energy can also be used to directly obtain particles of different sizes within a reasonable range according to actual needs, without stopping for reprocessing, thereby ensuring continuous preparation. On the other hand, the adjustable pulse energy can be used for the preparation of large quantities of raw materials, which is more conducive to mass production.
[0032] In addition, the preparation method of the present invention is also suitable for the controllable batch preparation of alloy catalysts. Compared with the traditional method, the ions of the alloy elements are reduced in the liquid phase system by adding a reducing agent. The problem is that different metal elements have different degrees of difficulty in being reduced, which makes it difficult to control the proportion of alloy elements in the prepared catalyst. What is more serious is that some transition metal elements are difficult to be reduced from ionic form. The present method can achieve the regulation of different alloy element components in the catalyst by replacing the target material. In addition, through the present method, the proportion of each element in the catalyst product can be directly and accurately controlled at the initial stage of the process to ensure that the alloy elements can enter the catalyst nanoparticles in the required amount and truly play the role of the alloy catalyst.
[0033] In addition, the alloy catalyst can reduce the amount of precious metal used while ensuring the catalytic performance, thereby reducing the cost of the catalyst. On the other hand, the alloy catalyst has its unique catalytic performance and stability, avoiding the shedding and deactivation of single-component precious metals. Moreover, the present invention fills inert gas during the preparation of metal nanoparticles, which can reduce the surface tension of the molten metal and accelerate evaporation, so that the metal forms ultrafine nanoparticles in the gas, thereby ensuring that the active component has a sufficient specific surface area, giving full play to the catalytic performance of the active metal component, and facilitating the subsequent loading process.
[0034] 5. The present invention adopts a planetary agitator in the final loading stage, that is, a stirring mill and a planetary mill. The two grinding methods are used in a superimposed manner, so that when some materials undergo grinding, crushing and extrusion, the whole material can flip and mix by itself, without artificial mixing, thereby ensuring the continuity of the process. The stirring mill and the planetary mill make the grinding medium in an irregular state of internal porous type. In this state, collision and shearing, as well as irregular movement, occur between the grinding medium and the particles, thereby breaking up the particles and distributing and combining them. Under this stirring mode, the active metal components and the carbon materials are more likely to combine with each other to form a crude catalyst. In addition, through high-temperature heat treatment at the end, the binding force between the active components and the carbon materials is strengthened, the atoms on the surface of the metal nanoparticles are reconstructed, and the atoms on the surface of the alloy particles migrate and segregate to form surface Pt-rich metal compounds, thereby improving the catalytic activity and stability. DETAILED DESCRIPTION
[0035] The present invention is described in further detail below.
[0036] Example 1
[0037] 1. Nitrogen is introduced into the arc plasma deposition equipment to achieve inert gas protection. 5g of metal Pt target is weighed and placed in the arc plasma deposition equipment. The voltage is adjusted to 100V and the capacitance is 200μF. The active metal Pt target is melted. The molten active metal Pt target is placed in a centrifugal oil mist collector and cooled to form metal Pt particles of about 5nm. Nitrogen is also introduced into the centrifugal oil mist collector to achieve inert gas protection. Then, the metal Pt particles are separated from the gas to obtain Pt nanoparticles.
[0038] 2. Weigh 20 g of XC-72R high-energy ball mill stirring container, introduce argon-hydrogen mixed gas with a hydrogen volume content of 5%, start the ball mill stirring for 5 hours to obtain enhanced activated carbon material;
[0039] 3. Add the Pt nanoparticles prepared in step 1 to the enhanced activated carbon material prepared in step 2, and place them in a planetary agitator. Use a stirred mill and a planetary mill to process for 1 hour respectively, so that the Pt nanoparticles are loaded on the enhanced activated carbon material to obtain a crude 20% catalyst;
[0040] 4. The crude 20% catalyst prepared in step 3 is subjected to high-temperature heat treatment at 200°C for 0.5h in an atmosphere of argon-hydrogen mixed gas with a hydrogen volume content of 5% to atomically reconstruct the Pt nanoparticles and improve the bonding between the Pt nanoparticles and the reinforced carbon material to form a fuel cell / water electrolyzer catalyst with a Pt loading of 20%.
[0041] Example 2
[0042] 1. Nitrogen is introduced into an arc plasma deposition device, 6 g of a metal Pt target and 2 g of a metal Ru target are weighed and placed in the arc plasma deposition device, the voltage is adjusted to 400 V, the capacitance is 2000 μF, the active metal Pt target and the Ru target are melted, the molten active metal Ru target is placed in a filter oil mist collector, and nitrogen is filled in, so that binary metal particles of about 2 nm are formed under an inert gas atmosphere, and then the binary metal particles are separated from the gas to obtain binary metal nanoparticles;
[0043] 2. Weigh 2 g of EC300 high-energy ball mill stirring container, introduce argon-hydrogen mixed gas with a hydrogen volume content of 5%, start ball milling and stirring for 1 hour to obtain enhanced activated carbon material;
[0044] 3. Add the binary metal nanoparticles prepared in step 1 to the enhanced activated carbon material prepared in step 2, and place them in a planetary agitator. Use a stirred mill and a planetary mill to process for 5 hours respectively, so that the binary metal nanoparticles are loaded on the highly activated carbon material to obtain a crude catalyst with a Pt content of 60%;
[0045] 4. The crude catalyst with a Pt content of 60% prepared in step 3 is subjected to high-temperature heat treatment at 500°C for 5 hours in an argon hydrogen atmosphere with a hydrogen volume content of 10% to atomically reconstruct the binary metal nanoparticles, thereby improving the bonding between the metal nanoparticles and the reinforced activated carbon material, and forming a fuel cell / water electrolyzer catalyst with a Pt loading of 60% and a mass ratio of metal Pt to metal Ru of 3:1.
[0046] Example 3
[0047] 1. Argon gas is introduced into an arc plasma deposition device, 3 g of a metal Pt target, 2 g of a metal Co target and 1 g of a metal Mn target are weighed and placed in the arc plasma deposition device, the voltage is adjusted to 300 V, the capacitance is 1000 μF, the active metal Pt target, the Co target and the Mn target are melted, and then ternary metal particles of about 3.5 nm are formed under an inert gas atmosphere, and the ternary metal particles are separated from the gas by a centrifugal oil mist collector and a filter oil mist collector to obtain ternary metal nanoparticles;
[0048] 2. Weigh 4 g of EC600 high-energy ball mill stirring container, introduce argon-hydrogen mixed gas with a hydrogen volume content of 5%, start ball milling and stirring for 3 hours to obtain enhanced activated carbon material;
[0049] 3. Add the ternary metal nanoparticles prepared in step 1 to the enhanced activated carbon material prepared in step 2, and process them by stirring mill and planetary mill for 3 hours respectively, so as to load the ternary metal nanoparticles on the highly activated carbon material to obtain a crude catalyst with a Pt content of 30%;
[0050] 4. The crude catalyst with a Pt content of 30% prepared in step 3 is subjected to high-temperature heat treatment at 400°C for 3 hours in an argon hydrogen atmosphere with a hydrogen volume content of 8%, so as to atomically reconstruct the ternary metal nanoparticles and improve the bonding between the metal nanoparticles and the reinforced activated carbon material to form a fuel cell / water electrolyzer catalyst with a Pt loading of 30% and a mass ratio of metal Pt, metal Co and metal Mn of 3:2:1.
[0051] Comparative Example 1
[0052] 1. Nitrogen is introduced into the arc plasma deposition equipment, 5 g of metal Pt target is weighed and placed in the arc plasma deposition equipment, the voltage is adjusted to 100 V, the capacitance is 200 μF, the active metal Pt target is melted, and then metal Pt particles of about 3 nm are formed under an inert gas atmosphere, and the metal Pt particles are separated from the gas by a centrifugal oil mist collector and a filter oil mist collector to obtain Pt nanoparticles;
[0053] 2. Weigh 20 g of XC-72R high-energy ball mill stirring container, introduce argon-hydrogen mixed gas with a hydrogen volume content of 5%, start the ball mill stirring for 5 hours to obtain enhanced activated carbon material;
[0054] 3. Add the Pt nanoparticles prepared in step 1 to the enhanced activated carbon material prepared in step 2, add 160 g of deionized water and 400 g of ethylene glycol; start stirring to evenly disperse the activated carbon material in the mixed solvent of deionized water and ethylene glycol, and start heating to keep the reaction temperature at 40°C;
[0055] 4. Weigh 0.2 g of sodium citrate and dissolve it in 9.8 g of deionized water, then add the sodium citrate aqueous solution into step 3 and carry out reduction reaction for 60 minutes;
[0056] 5. After the reaction is completed, cool it to room temperature 25°C, then filter it using a filter membrane with a pore size of 1 micron, wash it with deionized water for 3 times, and vacuum dry it at 60°C for 6 hours to obtain a catalyst with a Pt content of 20%.
[0057] Comparative Example 2
[0058] 1. Nitrogen is introduced into the arc plasma deposition equipment, 5 g of metal Pt target is weighed and placed in the arc plasma deposition equipment, the voltage is adjusted to 100 V, the capacitance is 200 μF, the active metal Pt target is melted, and then metal Pt particles of about 3 nm are formed under an inert gas atmosphere, and the metal Pt particles are separated from the gas by a centrifugal oil mist collector and a filter oil mist collector to obtain Pt nanoparticles;
[0059] 2. Weigh 20g of XC-72R and place it in a high-energy ball mill stirring container;
[0060] 3. Add the Pt nanoparticles prepared in step 1 to the XC-72R in step 2, and process them by stirring mill and planetary mill for 1 h respectively to load the Pt nanoparticles on the XC-72R to obtain a crude 20% catalyst;
[0061] 4. The crude 20% catalyst prepared in step 3 is subjected to high-temperature heat treatment at 200°C for 0.5h in an argon atmosphere with a hydrogen content of 5% to atomically reconstruct the Pt nanoparticles and improve the bonding between the Pt nanoparticles and XC-72R to form a fuel cell / water electrolyzer catalyst with a Pt loading of 20%.
[0062] Comparative Example 3
[0063] 1. Nitrogen is introduced into the arc plasma deposition equipment, 5 g of metal Pt target is weighed and placed in the arc plasma deposition equipment, the voltage is adjusted to 100 V, the capacitance is 200 μF, the active metal Pt target is melted, and then metal Pt particles of about 3 nm are formed under an inert gas atmosphere, and the metal Pt particles are separated from the gas by a centrifugal oil mist collector and a filter oil mist collector to obtain Pt nanoparticles;
[0064] 2. Weigh 20 g of XC-72R high-energy ball mill stirring container, introduce argon with a hydrogen content of 5%, start the ball mill stirring for 5 hours to obtain enhanced activated carbon material;
[0065] 3. Add the Pt nanoparticles prepared in step 1 to the enhanced activated carbon material prepared in step 2, and stir and mix for 1 hour to load the Pt nanoparticles on the enhanced activated carbon material to obtain a crude 20% catalyst;
[0066] 4. The crude 20% catalyst prepared in step 3 is subjected to high-temperature heat treatment at 200°C for 0.5h in an argon atmosphere with a hydrogen content of 5% to atomically reconstruct the Pt nanoparticles, thereby improving the bonding between the Pt nanoparticles and the enhanced activated carbon material, and forming a fuel cell / water electrolyzer catalyst with a Pt loading of 20%.
[0067] Comparative Example 4
[0068] Nitrogen is introduced into an arc plasma deposition device, 5 g of a metal Pt target is weighed and placed in the arc plasma deposition device, the voltage is adjusted to 50 V, the capacitance is 100 μF, the active metal Pt target is melted, the melted active metal Pt target is placed in a centrifugal oil mist collector, and nitrogen is filled in to form metal Pt particles of about 10 nm in an inert atmosphere, and then the metal Pt particles are separated from the gas to obtain Pt nanoparticles;
[0069] 2. Weigh 20 g of XC-72R high-energy ball mill stirring container, introduce argon-hydrogen mixed gas with a hydrogen volume content of 5%, start the ball mill stirring for 5 seconds, and obtain the enhanced activated carbon material;
[0070] 3. Add the Pt nanoparticles prepared in step 1 to the enhanced activated carbon material prepared in step 2, and place them in a planetary agitator. Use a stirred mill and a planetary mill to process for 1 hour respectively, so that the Pt nanoparticles are loaded on the strong activated carbon XC-72R to obtain a crude 20% catalyst;
[0071] 4. The crude 20% catalyst prepared in step 3 is subjected to high-temperature heat treatment at 200°C for 0.5h in an atmosphere of argon-hydrogen mixed gas with a hydrogen volume content of 5% to atomically reconstruct the Pt nanoparticles, thereby improving the bonding between the Pt nanoparticles and the enhanced activated carbon material, and forming a fuel cell / water electrolyzer catalyst with a Pt loading of 20%.
[0072] Test Example 1
[0073] The metal catalysts provided in the above Examples 1-3 and Comparative Examples 1-4 were prepared into fuel cells / water electrolyzers according to the following methods, and electrical performance tests were performed:
[0074] 1. Preparation of CCM for fuel cell / water electrolyzer: The catalysts prepared in Examples 1-3 were added to deionized water and a 5% mass concentration of a fully sulfonic acid resin solution, respectively, and fully ultrasonically dispersed and stirred to form a paste, and the slurry bubbles were removed under vacuum; then, the slurry was evenly coated on both sides of the Nafion@ series membrane to prepare CCM containing the catalyst of Example 1, CCM containing the catalyst of Example 2, and CCM containing the catalyst of Example 3, respectively, and the loading amounts were ensured to be the same;
[0075] 2. Single cell assembly and testing: Carbon paper treated with polytetrafluoroethylene hydrophobic treatment is used as the gas diffusion layer; the end plate is a gold-plated stainless steel plate. Each CCM, gas diffusion layer, collector plate, end plate and sealing material are assembled into a single cell. The single cell operating conditions are: proton exchange membrane fuel cell / water electrolyzer: H2 / air excess coefficient is 1.5 / 2.5, air back pressure is 0; anode and cathode humidification, humidity is 100%; single cell operating temperature is 80℃, humidification temperature is 60~75℃.
[0076] The test results are shown in Table 1.
[0077] Table 1 Catalyst performance test
[0078] Group <![CDATA[ 0.6V@Power Density In / cm 2 ]]> <![CDATA[0.7V @ power density W / cm 2 > Example 1 0.79 0.65 Example 2 0.82 0.68 Example 3 0.78 0.59 Comparative Example 1 0.60 0.51 Comparative Example 2 0.53 0.45 Comparative Example 3 0.34 0.23 Comparative Example 4 0.33 0.21 Commercial Pt / C (70%) 0.75 0.55
[0079] As can be seen from Table 1, the performance of the catalyst prepared by the solvent reduction method in Comparative Example 1 is relatively low, which is due to the influence of impurities such as reducing agents in the prepared catalyst; the carbon material in Comparative Example 2 has not been activated, and the specific surface area of the prepared catalyst is low, which seriously affects the catalytic performance; the solid phase reaction in Comparative Example 3 did not adopt effective grinding, and the amount of prepared carbon-supported catalyst was small, and most of them were still in a state of separation of carbon carrier and active metal components, and effective catalysis could not be achieved; the energy of the arc plasma deposition equipment in Comparative Example 4 was low, and the particles of the active components of the prepared catalyst were large, and its catalytic performance was poor.
[0080] In summary, the metal catalyst provided by the embodiment of the present invention has higher single cell performance than the commercial Pt / C catalyst. On the one hand, since the catalyst prepared by the present invention does not contain solvents and additives, no residue will remain. On the other hand, the metal active components and activated carbon in the catalyst prepared by the present invention are well combined, and the activation energy of the electrochemical reaction is low.
[0081] The above specific embodiments are merely explanations of the present invention and are not limitations of the present invention. After reading this specification, those skilled in the art may make modifications to the embodiments without any creative contribution as needed. However, such modifications are protected by the patent law as long as they are within the scope of the claims of the present invention.
Claims
1. A catalyst batch production method, characterized in that: The method comprises the following steps: A. The active metal target is melted under the protection of an inert gas, and then placed in an oil mist collector and an inert gas is introduced at the same time. After cooling, metal nanoparticles are formed, and then the metal nanoparticles are separated from the inert gas to finally obtain metal nanoparticles; B. ball-milling and stirring the carbon material and introducing an activated gas for activation treatment to obtain a reinforced activated carbon material; C. adding the metal nanoparticles obtained in step A to the enhanced activated carbon material obtained in step B, stirring and mixing by a planetary stirrer, so that the metal nanoparticles are loaded on the enhanced activated carbon material to obtain a loaded material; D. heat-treating the supported material obtained in step C in a mixed gas atmosphere to form a catalyst having a surface rich in active components; The carbon material is one of XC-72R, EC300, EC600, graphene, and carbon nanotubes; The active metal is any one of Pt, Ir, Pd, and Ru, or a combination of one or two of the non-precious metals Co, Cu, Fe, Mo, and Mn; In step A, the active metal target is melted by arc plasma deposition, and the discharge voltage of the arc plasma deposition is 100-400V and the capacitance is 200-2000μF; In step B, the activation gas is a mixed gas of hydrogen and argon, wherein the volume fraction of hydrogen is 5%.
2. The production method according to claim 1, characterized in that: The mass ratio of the active metal to the carbon material is 0.25-4.
3. The production method according to claim 1, characterized in that: In step A, the diameter of the metal nanoparticles is 2-5 nm; The inert gas is nitrogen or argon.
4. A production method according to claim 1, characterized in that: In step B, the ball milling stirring time is 1-5h.
5. The production method according to claim 1, characterized in that: In step C, the stirring mill and the planetary mill of the planetary agitator are both performed for 1-5 hours.
6. The production method according to claim 1, characterized in that: In step D, the heat treatment temperature is 200-500° C., and the heat treatment time is 0.5-5 h; The mixed gas is a mixed gas of hydrogen and argon, wherein the volume fraction of hydrogen is 5-10%.
7. A catalyst prepared by the production method according to any one of claims 1 to 6, characterized in that: The catalyst comprises an active carbon material and an active metal component, wherein the mass content of the active metal component is 20-80%.
8. Use of the catalyst according to claim 7 in a fuel cell or a water electrolysis cell.
Citation Information
Patent Citations
Method for preparing iron-carrying ordered mesoporous carbon materials
CN101580240A
Unsupported fuel cell catalyst slurry and preparation method thereof
CN101664698A